FOREIGN EXPERIENCE IN DIGITAL ECONOMY MANAGEMENT - Matniyazov Rakhim Razhabbaevich (Galaxy International Interdisciplinary Research Journal, 2022)
Foreign experience in managing the development of the digital economy is of quite serious interest, both in theoretical and practical terms. Today, in most developed countries, the paradigms for creating and further developing the digital economy differ significantly. The main directions in the field of regulation of management automation processes, which appear along with the formation and further development of the digital economy, lie in the new digital management system, which is directly dependent on legislation.